Situational Awareness (SA) Dalam Bridge Resources Management (BRM) Untuk Keselamatan Bernavigasi Kapal - Santoso, Wahyudi; Yulianto, Yulianto (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2024)
Ship accidents are still a problem in the maritime industry even though the BRM training program has been implemented since 2011. Analysis of several incidents noted that the human error factor was ranked highest. SA as an important aspect in BRM has not been applied properly as a related cause of the incident. For this reason, this study aims to foster and deepen the understanding of SA to the Ship's Crew and then apply it in BRM so that navigation safety is always maintained and similar incidents do not occur in the future. The study used a literature study method, by exploring references to maritime publications, previous journals, books and relevant sources. The results of the study, SA can be formed by mobilizing all five senses well combined with an understanding of the surrounding environment and experience. SA consists of 3 levels, each of which is interrelated and continuous, namely; Perception (Level 1), Understanding (Level 2) and Projection (level 3).